2019
DOI: 10.1126/sciadv.aav3502
|View full text |Cite
|
Sign up to set email alerts
|

Media exposure to mass violence events can fuel a cycle of distress

Abstract: The established link between trauma-related media exposure and distress may be cyclical: Distress can increase subsequent trauma-related media consumption that promotes increased distress to later events. We tested this hypothesis in a 3-year longitudinal study following the 2013 Boston Marathon bombings and the 2016 Orlando Pulse nightclub massacre using a national U.S. sample (N= 4165). Data were collected shortly after the bombings, 6 and 24 months post-bombings, and beginning 5 days after the Pulse nightcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
146
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(170 citation statements)
references
References 36 publications
16
146
0
8
Order By: Relevance
“…Akin to what we found when individuals reported distress associated with an approaching hurricane, (12) increased media exposure to an impending threat is associated with distress and more media consumption over time, potentially creating a cycle of distress, especially if the threat -like the pandemic -does not abate. (10) Studies have further demonstrated that subjective reports of acute stress following collective and individual traumas is associated with risk perceptions, (33) as well as subsequent physical health ailments, including higher risk of all-cause mortality. (34) Acute stress has been associated with subsequent cardiovascular illness in large population-based studies, (35) even when respondents' exposure to collective stress (i.e., 9/11 attacks) was primarily through the media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akin to what we found when individuals reported distress associated with an approaching hurricane, (12) increased media exposure to an impending threat is associated with distress and more media consumption over time, potentially creating a cycle of distress, especially if the threat -like the pandemic -does not abate. (10) Studies have further demonstrated that subjective reports of acute stress following collective and individual traumas is associated with risk perceptions, (33) as well as subsequent physical health ailments, including higher risk of all-cause mortality. (34) Acute stress has been associated with subsequent cardiovascular illness in large population-based studies, (35) even when respondents' exposure to collective stress (i.e., 9/11 attacks) was primarily through the media.…”
Section: Discussionmentioning
confidence: 99%
“…(2,(5)(6)(7) When faced with ambiguous, ongoing disasters like the COVID-19 pandemic, people often turn to the media for information to guide them, (8) making media a critical source of exposure to the crisis. Yet previous research demonstrates that exposure to media coverage of collective traumas such as mass violence, (9,10) infectious disease outbreaks, (11) or natural disasters, (12) may be a double-edged sword that can inform the public while simultaneously amplifying stress symptoms, worry, and perceived risk, with significant implications for public health. (13)(14)(15) Conflicting messages in the media may further exacerbate stress, (16) especially in the context of coping with life-threatening circumstances that could worsen as the pandemic unfolds over time.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever a public health event occurs, all kinds of information can be mixed, with novel, eye-catching information with some degree of uncertainty. Indeed, the nature of the media will make this type of information get more attention in more exaggerated ways (Thompson et al, 2019). When watching a lot of news regarding topics such as disasters, illness, and homelessness, people might experience empathy first and then symptoms similar to compassion fatigue, such as depression and anxiety to varying degrees (Kinnick, Krugman, & Cameron, 1996).…”
Section: Anxiety Information Uncertainty and Distance To The Epicentmentioning
confidence: 99%
“…The impact of the current global health emergency, termed COVID-19 by the World Health Organization (WHO), has significantly changed people's lives worldwide, casting a shadow over the mind of an enormous population. Although clarity and immediacy guaranteed the right to be informed, people are bombarded by various information and their moods enter a cycle of complexity (Thompson, Jones, Holman, & Silver, 2019). Encouraging slogan and unequivocal instruction can stabilize mood, while aversive news induces emotional responses to pain in others such as sadness and anxiety (Batson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Community groups argue that this is helping to fuel an arms race among London teenagers, who are inspired to acquire and carry more lethal weapons 36. If imitation is a pertinent factor in knife crime, the framing of the recent crisis as a “national epidemic” could export London’s knife crime problem to towns and cities across the country 3738…”
Section: Are We Fuelling the Fire?mentioning
confidence: 99%